Efficient harvesting of green microalgae cells by magnetic flocculated Fe3O4 nanoparticles combined with chitosan - Liu, Sifen; Fu, Suping; Wen, Zhongjie; Wang, Xiang; Jiang, Tianjiu; Liu, Hongye (International Journal of Agricultural and Biological Engineering, 2023)
Microalgae harvesting remains a challenging step in microalgae industrialization, thereby provoking the necessity to explore sustainable and economically feasible approaches. This research investigated the use of magnetic flocculated nanoparticles in the harvesting of the common microalgae Chlorella pyrenoidosa and Scenedesmus obliquus. The results showed that magnetic flocculated nanoparticles efficiently adsorbed negatively charged microalgae cells, and a magnetic field could adsorb the magnetic flocculated nanoparticles, thereby harvesting the microalgae cells. Harvesting efficiency was remarkably increased at the optimum magnetic field strength of 0.5 T with the magnetic flocculated nanoparticles at 0.738 g/L, and microalgae broth at pH 9.0, whereas the recovery rates of both C. pyrenoidosa and S. obliquus were around 97% and the sedimentation speed of both was above 2.63 cm/min. This study exemplified the magnetic flocculated nanoparticles-based approach to effectively harvest the microalgae cells. Keywords: magnetic flocculated nanoparticles, Chlorella pyrenoidosa, Scenedesmus obliquus, recovery rate, sedimentation speed DOI: 10.25165/j.ijabe.20231604.7809 Citation: Liu S F, Fu S P, Wen Z J, Wang X, Jiang T J, Li H Y. Efficient harvesting of green microalgae cells by magnetic flocculated Fe3O4 nanoparticles combined with chitosan. Int J Agric & Biol Eng, 2023; 16(4): 215-221